Contingency Management interventions for non-prescribed drug use during treatment for opiate addiction: A systematic review and meta-analysis. (1st September 2017) - Ainscough, Tom S.; McNeill, Ann; Strang, John; Calder, Robert; Brose, Leonie S.
Highlights: Contingency management (CM) reduces other drug use in opiate addiction treatment. Meta-analyses did not find evidence of effectiveness for non-prescribed opiate use. CM is effective for cocaine, tobacco, opiates + cocaine, tobacco, polysubstance use. Evidence is lacking for long-term effects. Abstract: Background and aims: Use of non-prescribed drugs during treatment for opiate addiction reduces treatment success, creating a need for effective interventions. This review aimed to assess the efficacy of contingency management, a behavioural treatment that uses rewards to encourage desired behaviours, for treating non-prescribed drug use during opiate addiction treatment. Methods: A systematic search of the databases Embase, PsychInfo, PsychArticles and Medline from inception to March 2015 was performed. Random effects meta-analysis tested the use of contingency management to treat the use of drugs during opiate addiction treatment, using either longest duration of abstinence (LDA) or percentage of negative samples (PNS). Random effects moderator analyses were performed for six potential moderators: drug targeted for intervention, decade in which the study was carried out, study quality, intervention duration, type of reinforcer, and form of opiate treatment. Results: The search returned 3860 papers; 22 studies met inclusion criteria and were meta-analysed. Follow-up data was only available for three studies, so all analyses used end of treatment data. Contingency management performed significantly better than control in reducing drug use measured using LDA ( d  = 0.57, 95% CI: 0.42–0.72) or PNS ( d  = 0.41) (95% CI: 0.28–0.54). This was true for all drugs other than opiates. The only significant moderator was drug targeted (LDA: Q = 10.75, p  = 0.03). Conclusion: Contingency management appears to be efficacious for treating most drug use during treatment for opiate addiction. Further research is required to ascertain the full effects of moderating variables, and longer term effects.